Elevated miRNA-21, miRNA-155, and miRNA-182 levels correlate with cytokine dysregulation in neurological disorders and indicate potential for biomarker and therapy development - Masoud Nikanfar; Mohammad Nouri; Mehdi Hassanpour; Jafar Rezaei; Alireza Nourazarian (Scientific Reports)
Abstract Cytokines and microRNAs (miRNAs) play a crucial function in neurological disorders. The purpose of this study was to investigate the interactions between cytokine networks and miRNA-21, miRNA-155, and miRNA-182 in the cerebrospinal fluid (CSF) of individuals with Parkinson’s disease (PD), Alzheimer’s disease (AD), and multiple sclerosis. Twenty patients diagnosed with MS, AD, and PD had CSF samples taken, while twenty healthy individuals served as controls. Cytokine levels (IL-6, TNF-α, IL-10, and CCL2) and miRNA expression were determined using an enzyme-linked immunosorbent test (ELISA) and qRT-PCR, respectively. The aim of this study was to identify the correlation between miRNA expression and cytokine levels.Compared with the control group, patients with MS and AD had significantly higher levels of miRNA-21, miRNA-155, and miRNA-182. The disease groups showed increased cytokine levels, particularly in AD and MS. Strong and statistically significant positive correlations were observed between miRNA-21 and IL-6 (r = 0.72, p < 0.001), miRNA-155 and TNF-α (r = 0.68, p < 0.001), and miRNA-182 and CCL2 (r = 0.75, p < 0.001) in all groups. This study provides new insights into the consistent patterns of miRNA expression and cytokine levels in the cerebrospinal fluid of individuals with neurological disorders. The significant correlations between certain miRNAs and cytokines suggest potential regulatory connections, offering valuable information on the pathogenesis of various diseases and identifying potential therapeutic targets.